2007
DOI: 10.1177/1532673x06297032
|View full text |Cite
|
Sign up to set email alerts
|

Latino Mobilization and Vote Choice in the 2000 Presidential Election

Abstract: Previous scholarship on Latino politics has demonstrated that mobilization has a statistically significant effect on voter turnout, suggesting the importance of get-out-the-vote campaigns to increase Latino political participation. Although nonpartisan organizations exist to mobilize Latino voters, most of the phone calls are made by political parties and candidates. I argue that the real test of effectiveness for partisan mobilization is vote choice. Using data from the 2000 presidential election, I model vot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 26 publications
(34 reference statements)
2
39
0
1
Order By: Relevance
“…Barreto (2007) (2006) found that Spanish language campaign commercials had a positive and significant impact on Latino turnout, however English commercials had no effect at all. With regard to vote choice in 2000, Nuño (2007) 187 and using strong anti-immigrant rhetoric the result was Latinos flocking to the Democratic Party (Barreto and Woods 2007). Thus, ethnic identity is, and will remain salient for Latinos vis-à-vis the political system for generations to come.…”
Section: Latino Ethnic Politicsmentioning
confidence: 99%
“…Barreto (2007) (2006) found that Spanish language campaign commercials had a positive and significant impact on Latino turnout, however English commercials had no effect at all. With regard to vote choice in 2000, Nuño (2007) 187 and using strong anti-immigrant rhetoric the result was Latinos flocking to the Democratic Party (Barreto and Woods 2007). Thus, ethnic identity is, and will remain salient for Latinos vis-à-vis the political system for generations to come.…”
Section: Latino Ethnic Politicsmentioning
confidence: 99%
“…In randomized field experiments, in-person canvassing tends to produce similar-sized boosts in Latino turnout as those found in studies of mostly White voters (Michelson, 2003;Ramirez, 2005). 2 A related and growing literature has documented that the Latino electorate is most effectively mobilized through interaction with other Latinos-whether candidates or campaign workers (Barreto, 2007;Nuño, 2007;Shaw et al, 2000;Barreto & Nuño 2011;Garza et al 2007)). What factors account for the efficacy of co-ethnic candidacy and outreach and explain why both appear to outperform generic mobilization tactics pursued by other organizations?…”
Section: The Role Of Language and Co-ethnicity In Mobilizing Latino Vmentioning
confidence: 72%
“…5 Dawson's argument seems incompatible with standard characterizations of human behavior being ''rational'' and ''self-interested,'' but an example from the party identification literature will shed light on predictive power, the notion of linked fate appears in several literatures. For example, Masuoka (2008), Nuño (2007), Sanchez (2006), and Stokes-Brown (2003, confirm that perceptions of linked fate are instrumental in mobilizing Latino political activism and informing Latinos' vote choice. Likewise, Junn (2008) and Junn and Masuoka (2008a, b) find that linked fate plays a similarly important role in shaping the political orientations of Asian citizens.…”
Section: Linked Fate and Disillusionment As Intersecting Pathways To mentioning
confidence: 99%